2021
DOI: 10.1002/pds.5235
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of adverse drug reaction reporting in Iran: Correction for underreporting

Abstract: Propose: Underreporting of Adverse Drug Reactions (ADRs) reduces the sensitivity of pharmacovigilance systems. We described ADR reporting and its trend from 1999 to 2017 and estimated the ADR underreporting in the Iranian Pharmacovigilance Center. Methods:We expressed the number of ADR reporting per inhabitants and admissions and their possible trends. Finally, ADR underreporting percentages were estimated by three approaches: prospective studies, literature review, stratification of the country; and the trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
(172 reference statements)
0
7
0
1
Order By: Relevance
“…A detailed description of study methodology has been previously reported [23,28]. The following provides a summary with relevant additional detail as needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of study methodology has been previously reported [23,28]. The following provides a summary with relevant additional detail as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Iran Food and Drug Administration established a national pharmacovigilance center in 1997 to receive spontaneous reports from healthcare professionals. Though, there is a considerable underreporting of ADRs to this spontaneous reporting systems [23].The leading cause of underreporting in Iran is unawareness of the existence of a national pharmacovigilance center [24,25], poor knowledge regarding reporting [26,27], and fear of punishment and criticism [26]. Thus, implementing active ADR detection and reporting in hospitals could be a constructive action in improving the awareness of unintended effects of medicines and patient safety and strengthening the national pharmacovigilance systems.…”
Section: Introductionmentioning
confidence: 99%
“…This review found that ADR reporting rates were low overall, suggesting underreporting by ADR reporters [ 23 , 79 ], which may be partly due to the passive nature of the reporting systems in these [ 59 ]. Underreporting points to the PV system’s inability to collate data on the safety, quality and effectiveness of marketed drugs that have not been tested outside the confines of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Underreporting is a concern worldwide because it causes the frequency of ADRs to be underestimated, delaying the detection of safety issues and therefore making it difficult to undertake a timely action [5,11]. Nevertheless, unlike spontaneous reporting, other tools such as active surveillance intentionally and continually search for the presence or absence of ADRs in a defined group of people; it thus allows the real incidence of ADRs to be known.…”
Section: Introductionmentioning
confidence: 99%